Case report: when two and ½ men go camping…. Issue 1 (December 2017) - von Rotz, Matthias; Dierig, Alexa; Heininger, Ulrich; Chrobak, Carl; Baettig, Veronika; Egli, Adrian
Abstract Background In patients, rapid identification of bacterial species may help to guide treatment at early stages. New protocols for the identification directly from positive blood culture flasks significantly helped in the presented case report. Case presentation Two patients (a father and son) presented with diarrhea, malaise, and fever of 3 to 4 days duration. Blood cultures from both patients cultured short Gram-positive rods. MALDI-TOF based rapid identification protocol direct from positive blood culture identifiedListeria monocytogenes as the cause of sepsis and could be confirmed with conventional methods.Listeria monocytogenes was identified 24 h later by conventional biochemical identification methods (VITEK 2). Antibiotic treatment was adjusted early in response to the MALDI-TOF based identification of bacteremia. Pulsed field gel electrophoresis confirmed the suspected relatedness of the father's and son's isolates. Conclusions MALDI-TOF based may provide a rapid identification of bacterial species directly from positive blood culture.